Oxymetry, time-motion and other indicators of exertion in elite handball referees during an official match - Estriga, M.; Carvalho, J.; Santiago, C. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The purpose of this study was to evaluate the physical exertion of handball referees in a live situation by combining different biometric indicators (HR, kinematics, oxygen consumption). Methods: Two male referees of EHF-level2 were involved in this study. An official match of the second national division was selected and special authorizations obtained. The referees and the players were familiarized with the experimental setup prior to the match. Three cameras (1024x768/24bit/30 fps) were placed in the arena ceiling and the live images processed with a new method for almost real-time video content extraction (Santiago et at., 2012), with a linear accuracy of 16 cm. The referees were equipped with tri-axial accelerometers (10bit/128Hz) and two channel ECG devices (10bit/256Hz). One of the referees was equipped with a portable oxymeter (Cosmed-K4b). After the match (<48 hours) the anaerobic threshold and maximal oxygen uptake of the referees was determined. Discussion: Kinematic analysis shows an overall covered distance per referee of 4.20km ± 1%, less than obtained for the first-level competitions (Estriga, 2012). The average velocity for the referee with the oxymeter was 3.70 km/h ± 1% while for the other referee was 3.40 km/h ± 1%. During 88% of the time the velocity was less than 9.0km/h and 7.2km/h (respectively). From the oxymetry we computed an energy expenditure of 200.34 kCal in the first half (33:33) and 188.42 kcal in the second half (36:08). This discrepancy of 6% is significant and similar to what we obtained from accelerometry and HR by the methods of (Brage et al. 2007). However the absolute values obtained by the two methods differ by 75% (overestimated by indirect methods). The results also show that in this population, the acceleration has a high correlation with the running speed. The HR is particularly sensitive to psychological stress situations.